Air pollutants and subsequent risk of chronic kidney disease and end-stage renal disease: A population-based cohort study. (June 2020) - Lin, Shih-Yi; Ju, Shu-Woei; Lin, Cheng Li; Hsu, Wu-Huei; Lin, Cheng-Chieh; Ting, I-Wen; Kao, Chia-Hung
Abstract: Air pollutants have been reported to be a possible risk factor of chronic kidney disease (CKD). However, epidemiologic results regarding acidic gases and CKD have yet to be elucidated. We linked the Taiwan Air Quality Monitoring Database (TAQMD) to the Longitudinal Health Insurance Database. An observational cohort of 161, 970 Taiwan citizens who had not been diagnosed with CKD was formed. The concentrations of air pollutant were classified into four levels based on quartile. Multivariable and univariable Cox proportional hazard regression models were used to assess the risk of developing CKD and end-stage renal disease (ESRD). Compared with Q1-level SO2, exposure to the Q4 level was at a 1.46-fold risk of developing CKD (95% confidence interval [CI] = 1.28–1.65) and 1.32-fold risk of ESRD (95% CI = 1.03–1.70). Compared with Q1-level NOx, exposure to the Q4 level was at a 1.39-fold higher risk of developing CKD (95% CI = 1.22–1.58) and 1.70-fold risk of ESRD (95% CI = 1.33–2.18). Compared with Q1-level NO, exposure to the Q4 level was at a 1.48-fold risk of CKD (95% CI = 1.30–1.68) and 1.54-fold risk of ESRD (95% CI = 1.20–1.98). Compared with Q1-level particles <2.5 μm (PM2.5), exposure to the Q4 level were at a 1.74-fold risk of CKD (95% CI = 1.53–1.98) and 1.69-fold risk of ESRD (95% CI = 1.32–2.16). Exposure to particulate and acidic gas air pollution was observed to be associated with an increased risk of CKD and ESRD. Highlights: Exposed to the Q4 level of SO2 with a 1.46-fold CKD risk and 1.32-fold ESRD risk. Exposed to the Q4 level of NOx with a 1.39-fold CKD risk and 1.70-fold ESRD risk. Exposed to the Q4 level of NO with a 1.48-fold CKD risk and 1.54-fold ESRD risk. Exposed to the Q4 level of PM2.5 with a 1.74-fold CKD risk and 1.69-fold ESRD risk. Air pollution was associated with an increased risk of CKD and ESRD.